Investigating English Learners’ Strategies to Promote Autonomy In Language Learning at Bilingual Socio-Politic Class Universitas Muhammadiyah Makassar - Rahmadani, Irfiani; Anugrawati, Nunung; Muchsin, Muhammad Arief (Journal of Language Testing and Assessment, 2023)
The aimed of this research was to find out the English learners strategies in language learning. The method used in this research was qualitative method. This research used observation and semi-structured interviews as instruments in collecting data. The subjects in this study were 3rd semester students in the bilingual class of the Department of State Administration. The research subjects consisted of 8 students. This study used a purposive sampling technique. The results of this study indicated that students used all types of strategies; memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies in language learning. The students used these strategies easy, convenient, practical, and effective for independent learning in language learning.